2016
DOI: 10.1097/scs.0000000000002423
|View full text |Cite
|
Sign up to set email alerts
|

Craniosynostosis Following Fetal Methotrexate Exposure

Abstract: Methotrexate (MTX) is an antimetabolite, folic acid antagonist that inhibits purine nucleotide production, DNA synthesis, and cellular proliferation. Despite widespread therapeutic uses, MTX remains a potent teratogen. Methotrexate embryopathy encompasses multiorgan system dysfunction, including intrauterine growth restriction as well as cardiac, craniofacial, renal, genital, and skeletal abnormalities. Effects of MTX exposure on fetal development continue to be described. This series of 4 patients with MTX-as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…Inhibited glutamyl to γ-carboxyglutamyl transition of vitamin K-dependent proteins such as osteocalcin and periostin (Hanumanthaiah et al, 2001;Fernandez et al, 2014) Craniofacial malformations of the nose and airways, eye/ear defects and cleft lip in humans when taken during the first trimester of gestation (Hou, 2004) 60 µM 4-96 hpf Shortened head structures, a dent in the anterior ethmoid plate, which also showed altered cell morphology and disorganized cell stacking Lee et al, 2013;Liu et al, 2020 Folic acid antagonist which inhibits DNA synthesis and cell proliferation by competitively inhibiting dihydrofolate reductase (Lee et al, 2012) Craniosynostosis and microcephaly and incomplete cleft palate in humans (Granzow et al, 2003;Zarella et al, 2016) Acetaminophen (Paracetamol) 2.5-13.4 mM 0-120/72-120 hpf Palatoquadral length, ceratohyal length and head size reduced Cedron et al, 2020 Activation cytochrome P450 and increased apoptosis (Cedron et al, 2020) No affected phenotypes reported Cyclosporin A (Immunmodulator)…”
Section: Pharmaceuticals and Teratogenesis In Zebrafish Larvaementioning
confidence: 99%
“…Inhibited glutamyl to γ-carboxyglutamyl transition of vitamin K-dependent proteins such as osteocalcin and periostin (Hanumanthaiah et al, 2001;Fernandez et al, 2014) Craniofacial malformations of the nose and airways, eye/ear defects and cleft lip in humans when taken during the first trimester of gestation (Hou, 2004) 60 µM 4-96 hpf Shortened head structures, a dent in the anterior ethmoid plate, which also showed altered cell morphology and disorganized cell stacking Lee et al, 2013;Liu et al, 2020 Folic acid antagonist which inhibits DNA synthesis and cell proliferation by competitively inhibiting dihydrofolate reductase (Lee et al, 2012) Craniosynostosis and microcephaly and incomplete cleft palate in humans (Granzow et al, 2003;Zarella et al, 2016) Acetaminophen (Paracetamol) 2.5-13.4 mM 0-120/72-120 hpf Palatoquadral length, ceratohyal length and head size reduced Cedron et al, 2020 Activation cytochrome P450 and increased apoptosis (Cedron et al, 2020) No affected phenotypes reported Cyclosporin A (Immunmodulator)…”
Section: Pharmaceuticals and Teratogenesis In Zebrafish Larvaementioning
confidence: 99%
“…This group showed that the use of sertraline and citalopram was associated with an increased risk of CS in the fetus. Zarella et al 34 also reported a series of cases showing premature fusion of the cranial sutures after fetal methotrexate exposure. Furthermore, this study reports that children who received folic acid as part of their chronic treatment had seven times higher odds of developing CS, which contrasts to what has been reported in the literature throughout the years, in which folic acid has not been significantly associated with CS development.…”
Section: Discussionmentioning
confidence: 98%
“…Aside from the extremity abnormalities, previous groups have described genitourinary, skeletal, and cardiovascular abnormalities, as well as anomalies including cleft lip, craniosynostosis, and other craniofacial malformations. 5,13,15 Studies comparing the incidence of deformities after MTX exposure to those present in the general population have concluded that there is a disproportionately higher incidence of pulmonary atresia, craniosynostosis, and limb deficiencies in patients exposed in utero to MTX. 8 Our series focuses on extremity abnormalities associated with MTX embryopathy.…”
Section: Discussionmentioning
confidence: 99%